(untitled) (Italian Journal of Public Health, 2010)
Background: Vancomycin-resistant enterococci (VRE), often responsible for nosocomial infections, have frequently been isolated from animal and vegetable foods. In our study we evaluated the antibiotic susceptibility of enterococci isolated from eight types of vegetables randomly selected from grocery stores in Naples. Methods: From July to November 2008, we analyzed 150 samples: the bacteria were isolated with standardized methods and antibiotic susceptibility was determined using the disc diffusion method. The resistance to vancomycin versus other antibiotics was assessed by the Kappa test. Results: 70% of the samples, mainly parsley (96.2%), showed enterococci. Of these, 59.1% belonged to the species Enterococcus faecium. Strains resistant to vancomycin and teicoplanin were isolated respectively in 47.6% and 49.5% of the samples: the first one mainly in curly endive (72.7%) and the second one in parsley (76.9%). Almost all the isolated strains showed resistance to methicillin (89%), kanamycin (82%) and cephalothin (68%). The Kappa test showed statistically significant associations between resistance to vancomycin and resistance to teicoplanin, erythromycin, methicillin, tetracycline and chloramphenicol. Conclusions: Because of the possible involvement of food in the transmission of resistant micro-organisms to human intestinal microbiota, our data may provide the basis for future studies.